Economic Analysis of Prices and Arrivals of Turmeric in Duggirala Market of Andhra Pradesh - Reddy, G. Raghunadha; Reddy, M. Chandrasekhar; Sneha, K. S.; Gita, B. Meher; Ramesh, D. (International Journal of Economic Plants, 2021)
Turmeric is an important spice grown in India since ancient times. It is also known for its medicinal value and used as an antiseptic since ancient times. India is apparently the largest consumer, producer and exporter of turmeric in the world. Turmeric is the third largest spice produced in India and largely concentrated in Telangana, Andhra Pradesh, Tamil Nadu, Karnataka etc. In this paper, an attempt has been made to study the arrivals and prices of turmeric in Duggirala market in Andhra Pradesh based on the secondary data during the period 2004-2019. The seasonal variations in the arrivals and prices were studied by seasonal indices with the help of ratio to moving average method. For the arrivals of turmeric in Duggirala market, seasonal indices were recorded maximum (206.44) during the month of May and minimum (50.32) in the month of October and prices were lowest (89.39) in the month of March and the highest (107 and 107.27) in November and December, respectively. The present study revealed that the power and cubic models were selected as the best fitted nonlinear models for prices and arrivals of turmeric in Duggirala market. Turmeric market price and arrivals in Duggirala Market for the year 2020 is estimated as INR 6827 quintal-1 and 82207 quintals-1, respectively.